Cultivation of organic tomato - Singh, R K; Singh, B; Chaubey, T; Rai, N (Indian Horticulture, 2018)
Many of the conventional pesticides and fertilizers persist in the soil andare harmful to the beneficial soil microorganism including earthworm,thereby resulting in degradation of soil fertility, increasing environmentaldegradation, pollution potential and health hazards. In such a situation,agriculture is shifting from chemical to organic farming, as well as demandfor organic vegetable production is also increasing day-by-day. Amongvegetables, cultivation of resistant tomato (free from diseases and pests) byorganic farming is a challenge for tomato growers. Organic farming is asystem that seeks to avoid the use of chemical fertilizers and pesticides.Tomato cultivated by organic farming produces healthy, nutritious andresidual free fruits. Organic tomatoes are always in high demand in bothlocal and whole-sale markets, and have been need of farmers for theireasy cost production and consumers for their good health.